Development and Validation of a Method for the Detection of α- and β-Endosulfan (Organochlorine Insecticide) in Calliphora vomitoria (Diptera: Calliphoridae). Issue 1 (4th October 2017) - Magni, Paola A; Pazzi, Marco; Vincenti, Marco; Converso, Valerio; Dadour, Ian R
Abstract: Entomotoxicology studies employ analytical methods and instrumentation to detect chemical substances in carrion insects feeding from the decomposing tissues. The identification of such chemicals may determine the cause of death and may be used for the estimation of the minimum time since death. To date, the main focus of entomotoxicological studies has been the detection of drugs, whereas little information concerns the effects of pesticides on blowflies. Pesticides are generally freely available and more affordable than drugs but they can also be a home hazard and an accessible candidate poison at a crime scene. A QuEChERS extraction method followed by Gas chromatography–mass spectrometry (GC-MS) analysis was developed for the detection of α- and β-endosulfan (organochlorine insecticide and acaricide) in Calliphora vomitoria L. (Diptera: Calliphoridae) and validated. Furthermore, the effects of endosulfan on the morphology, development time and survival of the immature blowflies were investigated. Larvae were reared on liver substrates homogeneously spiked with aliquots of endosulfan corresponding to the concentrations found in body tissues of humans and animals involved in endosulfan poisoning. Results demonstrated that the combination of QuEChERS extraction and GC-MS provide an adequate methods to detect both α- and β-endosulfan in blowfly immatures. Furthermore, the presence of α- and β-endosulfan in the food source 1) prevented C. vomitoria immatures reaching the pupal instar and, therefore, the adult instar at high concentrations, 2) did not affect the developmental time of blowflies at low concentrations 3) affected the size of immatures only at high concentrations, resulting in significantly smaller larvae.